APAKAH KINERJA DAN RISIKO REKSADANA SYARIAH LEBIH BAIK DIBANDINGKAN DENGAN REKSADANA KONVENSIONAL? - Dariyus Dariyus (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2012)
The growth of Islamic financial products has fueled as financial issues in the last recent years. This kind of products has been developed as the alternative of financial investment not only in the Islamic countries, but also in the non-islamic ones. This research provides one of the Islamic financial issues, especially equity fund, which traded on Indonesia Stock Exchange. The aim of this research is to compare investment on equity funds base on Islamic and conventional perpectives regarded to risk and performance measurers. The results show that conventional equity’s funds have higer risk and better performance than Islamic ones. According to these results, it reflects that conventional funds have more active strategic investment comparing to Islamic funds.